A source depletion model for vapor intrusion involving the influence of building characteristics. (March 2019) - Zhang, Ruihuan; Jiang, Lin; Zhong, Maosheng; DeVaull, George; Lahvis, Matthew A.; Ma, Jie; Zhou, Youya; Zheng, Rui; Fu, Quankai
Abstract: If volatile organic compound (VOC)-contaminated soil exists underneath a building, vapors may migrate upwards and intrude into the interior air of the building. Most previous models used to simulate vapor intrusion (VI) were developed by assuming that the source was constant, although a few recent models, such as the Risk-Based Corrective Action (RBCA) Tool Kit (TK) model, have been developed to consider source depletion (SD). However, the RBCA TK model ignores the effects of building characteristics due to its assumption that the ground is not covered by the actual building it models, which leads to incorrect results since the presence of the building affects the SD. In this study, a SD model is developed based on the three processes of VI while considering the impact of key building parameters on SD. The proposed model (i.e., the SD model) still follows the law of mass conservation, and the sensitivity analysis shows that the soil-building pressure differential (dP) is an important building characteristic that affects SD. Taking trichloroethylene (TCE) for simulation in the case of a soil concentration below the saturation concentration, as the soil permeability decreases, the differences in the results between the SD model and RBCA TK model decrease; as the Peclet number decreases, the effect of the dP on the results of the SD model decreases. The new model only accounts for the migration of contaminants at the source of depletion; therefore, the model is more applicable for these contaminants, which are considered to have low-biodegradable characteristics. Furthermore, since the model emphasizes the impact of buildings on the source, it is applicable when there is a considerable building area above the source, such as large commercial buildings or residential communities with underground parking lots, which exist in most cities. Graphical abstract: Image 1 Highlights: A source depletion model for vapor intrusion was proposed. The model considers the impact of building characteristics. The model still follows the law of mass conservation. The model is more applicable when the area of building is large. Abstract : A source depletion model for vapor intrusion that takes into account the impact of building characteristics was proposed.